2023
DOI: 10.1038/s42003-023-04536-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficient 3D light-sheet imaging of very large-scale optically cleared human brain and prostate tissue samples

Abstract: The ability to image human tissue samples in 3D, with both cellular resolution and a large field of view (FOV), can improve fundamental and clinical investigations. Here, we demonstrate the feasibility of light-sheet imaging of ~5 cm3 sized formalin fixed human brain and up to ~7 cm3 sized formalin fixed paraffin embedded (FFPE) prostate cancer samples, processed with the FFPE-MASH protocol. We present a light-sheet microscopy prototype, the cleared-tissue dual view Selective Plane Illumination Microscope (ct-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…After the cutting, the agarose surrounding each slice was removed. The permeabilization and staining protocols were modified from those of Murray et al, 2015 following the Costantini et al, 2021 [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] protocol, as described below. Samples were first incubated in the ice-cold SWITCH-OFF solution (4% glutaraldehyde (GA) in PBS 1 X and KHP 0.1 M, titrated with HCl to pH = 3) for 1 day at 4 °C with gentle shaking, then incubated for 1 day in the SWITCH-ON solution (0.5% GA in PBS 1 X, pH = 7.6) for 1 day at 4 °C with gentle shaking.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the cutting, the agarose surrounding each slice was removed. The permeabilization and staining protocols were modified from those of Murray et al, 2015 following the Costantini et al, 2021 [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] protocol, as described below. Samples were first incubated in the ice-cold SWITCH-OFF solution (4% glutaraldehyde (GA) in PBS 1 X and KHP 0.1 M, titrated with HCl to pH = 3) for 1 day at 4 °C with gentle shaking, then incubated for 1 day in the SWITCH-ON solution (0.5% GA in PBS 1 X, pH = 7.6) for 1 day at 4 °C with gentle shaking.…”
Section: Methodsmentioning
confidence: 99%
“…However, the compatibility of 3D histology was demonstrated with both fresh [ 15 ], formalin-fixed [ 16 ], and FFPE tissues [ 17 , 18 , 19 , 20 ]. In particular, iDISCO, or its variants, demonstrated high compatibility with both fresh and FFPE human tissues [ 19 , 21 , 22 , 23 ]; other methodologies working on fresh/formalin-fixed/FFPE include CUBIC [ 17 , 20 ], ACT-PRESTO [ 16 ], BABB [ 24 ], X-CLARITY [ 15 ], PACT [ 25 , 26 ], FACT [ 27 , 28 ], and MASH [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, significant progress has been made in addressing this challenge through recent advancements in the understanding of the chemical principles affecting probe penetration and the establishment of practical protocols. [19][20][21][22] Tissue clearing methods have assisted several proof-of-concept studies of 3D histopathology applied to cancer diagnosis, demonstrating that it has a potential to yield better clinical outcomes in comparison with conventional 2D histopathologic methods (Figure 3). Independent studies from multiple groups have demonstrated that 3D imaging data of cancer patient-derived lymph nodes can enhance the diagnostic accuracy for detecting micrometastases by 14.8% 18 or 19% (Figure 3C,D).…”
Section: D His Topathology: E Xpanding the Limitati On Of Conventi On...mentioning
confidence: 99%
“…The challenge of achieving efficient penetration of fluorescent probes in 3D samples is ongoing. However, significant progress has been made in addressing this challenge through recent advancements in the understanding of the chemical principles affecting probe penetration and the establishment of practical protocols 19–22 …”
Section: D Histopathology: Expanding the Limitation Of Conventional 2...mentioning
confidence: 99%
“…A large volumetric tumor tissue becomes optically transparent using a chemical immersion or lipid-removal method that enables matching the refractive indexes (RIs) of tumor components to either oil or water phase 26, 27 . Such optically cleared tumor tissue can be practically used for visualizing detailed 3D architecture of the TME at cellular resolution by applying various fluorescence microscopy methods, including confocal and light-sheet microscopy 28, 29, 30 . However, despite providing high dimensional image data, multiplexing capability of current 3D tissue microscopy is restricted to the number of imaging channels in a fluorescence microscope as well as the available fluorophores having different excitation and emission wavelengths, which normally allows for imaging only 3 or 4 cell markers in a 3D tumor tissue.…”
Section: Introductionmentioning
confidence: 99%